Potensi Pengembangan Antioksidan/Antidiabetes Turunan Piridazinon sebagai Agen yang Menjanjikan untuk Terapi Penyakit Diabetes: Review - Fatisa, Yuni; Frimayanti, Neni; Teruna, Hilwan Yuda; Jasril , Jasril (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
Hyperglycemia can induce oxidative stress that can develop towards the pathogenesis of diabetic complications. Treatment strategies usually use antidiabetic and antioxidant drugs to help manage diabetes in patients. The discovery of drugs with dual activity properties will work on two targets at once and can minimize side effects. This review analyzes the potential for developing new antidiabetic and antioxidant agents from pyridazinone derivative compounds. The literature review study methodology uses the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) technique. Electronic database searches were conducted through Google Scholar, PubMed, and Science Direct to obtain relevant literature until 2024. The inclusion criteria were pyridazinone derivatives as antidiabetics and antioxidants using in silico, in vitro, and in vivo tests. A total of 24 original research journals have been described for the discussion of this review. The review results found that pyridazinone derivatives have the potential as α-Glucosidase inhibitors, antihyperglycemic, and aldose reductase inhibitors with moderate-strong activity levels. Several studies have also found that pyridazinone derivatives are antioxidants. These results are supported by the prediction through molecular docking approach studies. However, only two studies have reported pyridazinone derivatives that have antidiabetic and antioxidant properties at the same time. There is a connection between the active groups bound to the pyridazinone ring and the strength of its pharmacological effects. This review opens up opportunities for the potential development of pyridazinone derivatives with dual bioactivity. In addition, broader and deeper research with structural modification of pyridazinone derivatives as candidate therapeutic agents for diabetes patients needs to be continued.